Improving Wikipedia with DBpedia - Torres, Diego (2012)
DBpedia is the semantic mirror of Wikipedia. DBpedia extracts information from Wikipedia and stores it in a se- mantic knowledge base. This semantic feature allows com- plex semantic queries, which could infer new relations that are missing in Wikipedia. This is an interesting source of knowledge to increase Wikipedia content. But, what is the best way to add these new relations following the Wikipedia conventions? In this paper, we propose a path indexing algorithm (PIA) which takes the resulting set of a DBPedia query and discovers the best representative path in Wikipedia. We evaluate the algorithm with real data sets from DBpedia.